Operative immersion towards safety management: a case study at offshore / Nur Dalila Adenan ... [et al.] - Adenan, Nur Dalila; Mohd Said, Nur Shafini; Omar Ali, Siti Rapidah; Abdul Manaf, Suhaily Maizan (2018)
Safety in the workplace has long been a top concern for every industry. Zero accident ultimately a dream of safety professionals. Data obtained from SOCSO Annual Report 2016, showed that the total of 35 304 industrial accidents reported increased by 3.26% from the previous year. Hence, this study was undertaken to examine the level of operative immersion towards safety management covering three main aspects, namely the employees' perception, employees' knowledge, and employees' motivation. A set of questionnaires was distributed to 82 respondents who were offshore workers in one of the offshore service providers to the oil and gas industry in Malaysia. Data was analysed using reliability, descriptive statistics, regression and inferential statistical data via Statistical Package for Social Science (SPSS) version 21.0. Overall, the findings showed that the level of understudy was positive (moderate). Empirical test showed that all three variables had significant relationship and employee's knowledge was the most significant factor that influenced safety management. Based on the findings obtained, it is hoped that the study will benefit all parties involved in enhancing offshore security practices from time to time and some suggestions have been forwarded to assist further research in the future. Consequently, this study may help employer be more proactive in ensuring the employee involvement in safety and health management at the workplace.